A Constitution in full : recovering the unwritten foundation of American liberty - Lawler, Peter Augustine; Reinsch, Richard M. (American political thought., 2019)
""Peter A. Lawler and Richard M. Reinsch have identified the malady plaguing American constitutionalism in our day: a desiccated Lockeanism that makes an idol of individual choice at the expense of political life. Equally important, they have found a remedy in the unwritten constitution as well as the rich and neglected thought of Orestes Brownson. This study is a fitting denouement of Lawler's vast and deep corpus of work, and in making A Constitution in Full an indispensable book in full, Reinsch has proven himself a worthy successor to the scholar who taught him and so many others so much."